2016
DOI: 10.1007/978-3-319-46282-0_13
|View full text |Cite
|
Sign up to set email alerts
|

A Viewpoint Approach to Symbolic Music Transformation

Abstract: Abstract. This paper presents a general approach to the transformation of symbolic music. The method is based on viewpoints, which enable the representation of musical surfaces by sequences of abstract features. Along the transformation process, some of these sequences are conserved while some others are variable and can be replaced by generated ones. The initial piece is therefore seen as a template which is instantiated at each transformation. The method is illustrated in the paper with the particular case o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…In the last step new created harmonic development in dictionary h3 is combined with dictionary r2 of rhythm of the second MIDI file resulting in a new musical composition with regularity/consistency and development. This is the principal advantage of applying a transformational compositional method, where the source composition is taken as a seed and a new composition is obtained by transforming its features [26]. The following descriptions cover the proposed approach in further detail.…”
Section: Preliminary Considerationsmentioning
confidence: 99%
“…In the last step new created harmonic development in dictionary h3 is combined with dictionary r2 of rhythm of the second MIDI file resulting in a new musical composition with regularity/consistency and development. This is the principal advantage of applying a transformational compositional method, where the source composition is taken as a seed and a new composition is obtained by transforming its features [26]. The following descriptions cover the proposed approach in further detail.…”
Section: Preliminary Considerationsmentioning
confidence: 99%
“…A system for reharmonizing uplifting trance music based on a newly generated chord sequence was developed by [Bigo and Conklin 2015]. The system was extensively tested in an empirical study, in which Agres et al [2016] found that repetitiveness in harmonic structure and tension, not solely rhythmic structure, is a contributor to listener enjoyment in this form of electronic dance music.…”
Section: General Harmonizationmentioning
confidence: 99%
“…Through the use of start and end markers within the music segments some authors support music navigation, editing and synchronization [21][22][23][24]. Others develop applications for computer-assisted composition and improvisation [25][26][27][28]. In [29] authors study patterns and metrics characterizing musical aspects such as pitch, timbre, and loudness in a specific musical corpus.…”
Section: Related Workmentioning
confidence: 99%